Developing a website for English-speaking practice to English as a foreign language learners at the university level - Fauzi, Iwan; Asi, Natalina (Institute of Advanced Engineering and Science, 2025)
This study explored the adaptation of the ADDIE instructional model in designing and developing a website for the speaking practice of EFL students at the university level. The feasibility of the website was measured through the evaluation of independent experts from three aspects of rating: web design, instructional content, and language usage. Six lecturers and 64 EFL students were invited to evaluate the website. Two lecturers have expertise in multimedia and informatics, while the four others are two experts in instructional content of English teaching and two lecturers in English linguistic expertise. The assessments exposed that the web is easy to use by students and very practical in supporting students for learning; the content of learning material in the website has manifested the syllabus of English-speaking skill on the specified level; and the language used by the website is matched with the level of students’ language proficiency. Therefore, this study successfully developed a prototype of a web-based language learning product that helps students practice English speaking at the intermediate level.